Integrated Physiological and Transcriptomic Analyses Responses to Altitude Stress in Oat (Avena sativa L.) - Jinqiu, Yu; Bing, Li; Tingting, Song; Jinglei, He; Zelai, KongLing; Lu, Lian; Wenhua, He; Tao, Hai; Xinyu, Huang; Zengqing, Liu; Guowen, Cui; Yajun, Chen (Frontiers in Genetics, 2021)
Oat is an annual gramineous forage grass with the remarkable ability to survive under various stressful environments. However, understanding the effects of high altitude stresses on oats is poor. Therefore, the physiological and the transcriptomic changes were analyzed at two sites with different altitudes, low (ca. 2,080 m) or high (ca. 2,918 m) respectively. Higher levels of antioxidant enzyme activity, reactive oxygen and major reductions in photosynthesis-related markers were suggested for oats at high altitudes. Furthermore, oat yields were severely suppressed at the high altitude. RNA-seq results showed that 11,639 differentially expressed genes were detected at both the low and the high altitudes in which 5,203 up-regulated and 6,436 down-regulated. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment tests were conducted and a group of major high altitude-responsive pigment metabolism genes, photosynthesis, hormone signaling and cutin, suberine and wax biosynthesis were excavated. Using quantitative real-time polymerase chain response, we also confirmed expression levels of 20 DEGs (qRT-PCR). In summary, our study generated genome-wide transcript profile and may be useful for understanding the molecular mechanisms of Avena sativa L. in response to high altitude stress. These new findings contribute to our deeper relevant researches on high altitude stresses and further exploring new candidategenes for adapting plateau environment oat molecular breeding.